Equine conidiobolomycosis: A review and case study. (6th November 2020) - Zetterström, S.; Hanson, R.; Velloso Alvarez, A.; Caldwell, F.; Boone, L.; Schumacher, J.
Summary: Conidiobolus coronatus is one of the most commonly identified upper respiratory fungal pathogens in horses. This article includes a review of clinical signs, diagnostics, treatment and outcomes in previously reported cases of equine conidiobolomycosis, as well as six additional cases seen at our hospital. Each of the six horses presented with a complaint of serosanguinous or haemorrhagic nasal discharge and conidiobolomycosis was confirmed by histopathology and fungal culture. Five horses recovered after administration of antifungal drugs alone (n = 4) or in combination with extensive nasal septum resection (n = 1). Surgical treatment alone was ineffective. One horse was euthanised without treatment because of the extent of the disease.